Center pivot irrigation management in maize hybrids and the incidence of stalk rot - Kuhn, Irineu E. [UNESP]; Cotrim, Mayara F. [UNESP]; Gava, Ricardo; Alvarez, Rita de C. F.; Oliveira, Job T. de; Teodoro, Paulo E. (Univ Federal Campina Grande, 2020)
This study aimed to verify the incidence of Fusarium spp. in commercial maize hybrids and irrigation management strategies utilizing center pivot systems. The experiment was carried out during the second season in a randomized block design with a split-plot arrangement with five maize hybrids (2B810, MG580, AS1633, DKB290, and AG8544). The plots were irrigated with five frequencies (1, 2, 3, 4, and 5 days) in one experiment, and five water depths (at 25, 50, 75, 100, and 125% of crop evapotranspiration) in another experiment. Plant height, ear insertion height, moisture at harvest time, yield, and incidence of stalk rot were evaluated. Neither irrigation frequency nor irrigation depth influenced the incidence of disease. The one-day irrigation frequency provided the highest yield for maize hybrids. Hybrid 2B810 showed the highest yield and the lowest incidence of the disease.
Keywords: Zea mays; fungal disease; precision irrigation